USING OFF SCREENS - Erdem, Can (Sport- és Egészségtudományi füzetek, 2025)
How you play the game is more important than what you play. When using off screens you need to be an “actor”, to put the defence in a reacting situation (footwork is really important). Using the screen the right way is the key, but even if you want to create for someone, first you need to be a scoring threat. Different ways of using the screens are the key of the off screen actions. The passer shouldn’t hold the ball early, he/she should decide while dribbling, keeping the dribble alive. The receiver is the actor - needs to contact the defender always (make the “T” with the body: the offensive player’s shoulder touches the defensive player’s chest), and also must change the speed (from 0 to 100). Apart from changing speed, going close to the screener is important (must adjust speed when using stagger screens 0-40-0-100). When you are a receiver you need to see the court and the ball, you can’t look at the defenders, you must feel them. When using floppy screens is important first to fake the opposite side of the screen. Another teaching point is using the screen and setting the screen. The screener must fake the opposite side before setting the screen, the receiver must wait for the screen till it is firmly set. If you are in the proper position the alternatives are coming up (timing and spacing are the key). You have to make everyone believe that you are the scoring threat. First, we need to teach the fundamentals. Regardless of what kind of screens we are using, as long as we know how we play, what we play is less important. Using screens you need to make believe everyone that you are the scoring threat.